2022
DOI: 10.1002/dac.5304
|View full text |Cite
|
Sign up to set email alerts
|

Outage analysis of cooperative NOMA system with imperfect successive interference cancellation and channel state information over Rayleigh fading channel

Abstract: Summary Cooperative communication is a significant technology for fifth generation (5G) and beyond wireless communication to improve the quality of service (QoS) in massive networks. In addition, it serves as a promising candidate along with non‐orthogonal multiple access (NOMA) scheme to increase the spectral efficiency. Conventionally, cooperative‐NOMA (C‐NOMA) systems are analysed by assuming perfect successive interference cancellation (SIC) and imperfect SIC (I‐SIC) over Rayleigh, Rican, α−μ, Hoyt fading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The performance of a near-far relay C-NOMA system is explored using a Rayleigh fading channel, perfect and imperfect channel state information, and SIC, albeit only for a single user [18]. The usage of a half-duplex MIMO C-NOMA system with just a partial grasp of the channel state, as well as outage probability (OP) over Nakagami-m fading channels, is explored in [19]. The results, on the other hand, showed that the power allocation coefficients (PLCs) of users who were physically close to the BS were all assigned the same value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of a near-far relay C-NOMA system is explored using a Rayleigh fading channel, perfect and imperfect channel state information, and SIC, albeit only for a single user [18]. The usage of a half-duplex MIMO C-NOMA system with just a partial grasp of the channel state, as well as outage probability (OP) over Nakagami-m fading channels, is explored in [19]. The results, on the other hand, showed that the power allocation coefficients (PLCs) of users who were physically close to the BS were all assigned the same value.…”
Section: Introductionmentioning
confidence: 99%
“…Here is a quick rundown of our most significant contributions: − The OPs for the 2 users' NOMA and C-NOMA systems are generally represented in closed form by theoretical analysis with varying distances and PLCs. However, the simulation demonstrates that the derived OP expressions are more exact than those in [19]. − This paper proposes an opportunistic suboptimal relay selection technique that considers both users.…”
Section: Introductionmentioning
confidence: 99%